Nanofluids flow driven by peristaltic pumping in occurrence of magnetohydrodynamics and thermal radiation. (September 2019) - Prakash, J.; Siva, E.P.; Tripathi, D.; Kothandapani, M.
Abstract: A mathematical model is presented to study the nanofluids flow driven by peristalsis mechanisms through asymmetric channel. The electrically-conducting nature of the nanofluid demands magnetohydrodynamic effects. Governing equations contain the fluxed consequences of Brownian motion and thermophoretic dispersion of nanoparticles. To examine the thermal radiation effects, a thermal radiative flux model is also deployed. A lubrication approach is employed to simplify the non-linear terms. The analytic solutions are obtained using Homotopy Perturbation Method (HPM). The influences of heat source/sink, Biot number and thermal radiation on velocity profile, temperature profile, and nanoparticle concentration are computed. Trapping phenomenon is inherent mechanism of the peristaltic pumping, is also analyzed under the effects of pertinent parameters. A validity of HPM solutions for temperature of the nanofluid is made with numerical solution obtained by MATLAB through bvp4c. The outcomes show that nanoparticles concentration increases with increasing the strength of Biot number. The computations of present study are relevant to bio-inspired nanofluid smart pump designs which may also be exploited in spacecraft applications, biological smart drug delivery etc.